Perception of Parental Attitudes and General Academic Achievement of High School Students: a Russian-Kyrgyz Study - Tikhomirova, T.N.; Malykh, S.B. (Socialʹnaâ Psihologiâ i Obŝestvo, 2024)
Objective. Cross-cultural analysis of the perception of parental attitudes and its influence on the general academic performance of high school students from Russia and Kyrgyzstan. Background. The characteristics of parental attitudes are closely related not only to the child's educational success during life in the family, but also to educational achievements in the future. At the same time, the sociocultural specifics of parent-child relationships, through the perception of a growing child, can change the direction and magnitude of such associations. Study design. The characteristics of the relationship between mothers and fathers - emotional acceptance and overprotection - by high school students from two countries differing in socio-economic status are analyzed. A cross-cultural analysis of the structure of associations between the characteristics of the perception of parental attitudes and academic performance is carried out. Participants. The study analyzed data from 528 students in grades 10-11 from Russia and Kyrgyzstan. Russian sample: 230 people (M = 17,31; SD = 0,7), 58,1% girls. Kyrgyz sample: 298 people (M = 17,21; SD = 0,7), 67,6% girls. Measurements. Russian-language version of the questionnaire "Parental Bonding Instrument" (T.N. Tikhomirova, D.A. Gaysina, S.B. Malykh, 2021). Results. At high school age, the perception of parental attitude has a culture-specific conditioning, most clearly expressed in the perception of emotional acceptance by the mother and the overprotective attitude of the father. Conclusions. Given the existence of a universal model of the influence of parental attitudes on the general academic performance of high school students, cross-cultural specificity of functional associations within the model is observed, which is more characteristic of the perception of the attitudes of fathers rather than mothers. Цель. Кросс-культурный анализ восприятия родительского отношения и его влияния на общую академическую успеваемость старших школьников из России и Кыргызстана. Контекст и актуальность. Особенности родительского отношения тесно связаны не только с учебными успехами ребенка в процессе жизни в семье, но и с образовательными достижениями в дальнейшем. Вместе с тем социокультурная специфика детско-родительских взаимоотношений через восприятие взрослеющим ребенком может изменять направление и величину таких связей. Дизайн исследования. Анализируются особенности восприятия отношения матерей и отцов - эмоционального принятия и гиперопеки - старшеклассниками из двух государств, различающихся социально-экономическим статусом. Проводится кросс-культурный анализ структуры связей между особенностями восприятия родительского отношения и успеваемостью. Участники. В исследовании анализировались данные 528 обучающихся 10-11 классов из России и Кыргызстана. Российская выборка: 230 человек (M = 17,31; SD = 0,7), 58,1% девушек. Кыргызская выборка: 298 человек (M = 17,21; SD = 0,7), 67,6% девушек. Методы. Русскоязычная версия опросника «Юношеский отчет о родительском отношении» (Т.Н. Тихомирова, Д.А. Гайсина, С.Б. Малых, 2021). Результаты. В старшем школьном возрасте восприятие родительского отношения имеет культуроспецифичную обусловленность, наиболее ярко выраженную при восприятии эмоционального принятия матерью и гиперопекающего отношения отца. Основные выводы. При существовании универсальной модели влияния родительского отношения на общую академическую успеваемость старшеклассников наблюдается кросс-культурная специфика функциональных связей внутри модели, характерная в большей мере для восприятия отношения отцов, а не матерей.